Recombinant SARS-CoV-2 Delta/Omicron BA.5 emerging in an immunocompromised long-term infected COVID-19 patient - Ignacio Garcia; Jon Bråte; Even Fossum; Andreas Rohringer; Line V. Moen; Olav Hungnes; Olav Fjære; Kyriakos Zaragkoulias; Karoline Bragstad (Scientific Reports)
Abstract The emergence of the SARS-CoV-2 virus led to a global pandemic, prompting extensive research efforts to understand its molecular biology, transmission dynamics, and pathogenesis. Recombination events have been increasingly recognized as significant contributor to the virus’s diversity and evolution, potentially leading to the emergence of novel strains with altered biological properties. Indeed, recombinant lineages such as the XBB variant and its descendants have subsequently dominated globally. Therefore, continued surveillance and monitoring of viral genome diversity are crucial to identify and understand the emergence and spread of novel strains. Through routine genomic surveillance of SARS-CoV-2 cases in Norway, we discovered a SARS-CoV-2 recombination event in a long-term infected immunocompromised COVID-19 (coronavirus disease) patient. A deeper investigation showed several recombination events between two distinct lineages of the virus, namely AY.98.1 and BA.5, that resulted in a single novel recombinant viral strain with a unique genetic signature. Our data is consistent with the presence of several concomitant recombinants in the patient, suggesting that these events occur frequently in vivo. This study underscores the importance of continued tracking of viral diversity and the potential impact of recombination events on the evolution of the SARS-CoV-2 virus.